Development of A Problem-Based Learning Model to Improve Students’ Numeracy and Self-Efficacy - Citra Ayu Fatimah; Heri Retnawati (PRISMA, 2025)
Education in Indonesia requires development, particularly in students’ numeracy skills and self-efficacy (SE). The importance of numeracy skills is stated in the Graduate Competency Standards (SKL). Moreover, numeracy skills are also related to students’ self-efficacy. Students with good numeracy skills tend to have high self-efficacy, and students with poor numeracy skills generally have low self-efficacy. Based on these factors, it is necessary to develop an appropriate learning model. The aim of this study is to develop a problem-based learning (PBL) model to enhance students’ numeracy skills and self-efficacy, and to determine the feasibility of the developed product in improving students’ numeracy and self-efficacy. This development research follows the ADDIE stages: Analyze, Design, Develop, Implement, and Evaluate. The research methods used were both quantitative and qualitative. Quantitative methods were employed to determine the level of feasibility of the developed product, while qualitative methods were used to describe the calculated feasibility scores, suggestions and comments from validators, teachers, and students. The results showed that the developed product met the criteria of validity and practicality but did not meet the criteria of effectiveness. The ineffectiveness of the product was due to students not being accustomed to using the PBL model and their unfamiliarity with discussion-based learning.